Lifestyle and environmental stress as determinants of hypertension development in rural Indonesia: a multinomial logistic regression analysis - Mulyati, Lia; Rosalia, Linda; Hendriana, Yana (Poltekkes Kemenkes Bandung, 2026)
Background: Global evidence indicates that lifestyle behaviors and environmental stress contribute to blood pressure regulation; however, studies examining their combined effects on hypertension severity, particularly in rural Indonesian populations, remain limited. Objective: This study addresses this gap by applying multinomial logistic regression to predict hypertension stages and examine interactions between lifestyle and environmental stress. Methods: A cross-sectional study was conducted among 373 adults with hypertension aged ≥45 years in three rural villages in Kuningan Regency, Indonesia, selected through purposive sampling. Lifestyle behaviors and environmental stress were assessed using validated questionnaires with acceptable internal consistency (Cronbach’s α> 0.70). Blood pressure was classified into Stage 1, Stage 2, and Stage 3 hypertension. Multinomial logistic regression analyses adjusted for age, sex, body mass index, and hypertension duration were performed to estimate main and interaction effects. Results: The model demonstrated strong predictive validity (χ²= 174.10; p< 0.001). A healthy lifestyle was significantly associated with higher odds of Stage 1 (OR= 30.04) and Stage 2 hypertension (OR= 11.45) compared with Stage 3. Mild to moderate environmental stress also showed a protective association with hypertension severity (p< 0.01). A significant lifestyle–stress interaction (p< 0.05) indicated that a healthy lifestyle attenuated the adverse effects of severe stress, maintaining a high predicted probability of milder hypertension (0.67). Conclusion: These findings provide empirical evidence from rural Indonesia that lifestyle behaviors and environmental stress function as independent and interactive predictors of hypertension severity, supporting adaptive and health promotion frameworks and community-based interventions aligned with Sustainable Development Goal 3.